Analisis Bibliometrik Arah dan Perkembangan Penelitian Bertema Lembaga Keuangan Mikro Syariah di Indonesia Tahun 2013-2022 - Tulasmi Tulasmi; Siti Komariyah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to analyze the trends, and directions of research developments regarding Islamic microfinance institutions in Indonesia indexed in Google Scholar from 2013 to 2022. The data analysis method used is the bibliometric analysis, in which the data analysis will determine the most frequently researched topics which is still rarely investigated in research, especially in journals article on the role of Islamic microfinance institutions in poverty. The data analysis tool used is VOSviewer. The results show that the development of research for ten years has increased, the total number of researches from Google Scholar data is 353 studies, of which there are 137 research journal publications. The name of the author who has produced the most works is Edi Susilo; as many as five studies and the direction of development of keywords that are still rare and not yet diverse discussing the topic of Islamic microfinance institutions are capital, economic empowerment, micro small and medium enterprise (MSME), and ZIS.